Preparation and spectroscopic identification of the cyclic carbon dioxide dimer 1,2-dioxetanedione - Gerbig, Dennis; Justus Liebig University Giessen (My University, 2023)
Matrix isolation spectra as ASCII data point files in simple xy-format. Files can be opened and plotted by any combination of text editor and plotting program, respectively. Spectra were recorded on a Bruker Invenio R infrared spectrometer in conjunction with the Bruker OPUS 8.5 SP1 software.
Keywords: matrix isolation; physical organic chemistry; firefly; chemiluminescence; bioluminescence; reactive intermediate; infrared spectroscopy; cryogenic spectroscopy; dioxetane; ddc:500; ddc:500; ddc:540; ddc:570